2020
DOI: 10.1021/acsomega.0c04181
|View full text |Cite
|
Sign up to set email alerts
|

Ni-Catalyzed Reductive and Merged Photocatalytic Cross-Coupling Reactions toward sp3/sp2-Functionalized Isoquinolones: Creating Diversity at C-6 and C-7 to Address Bioactive Analogues

Abstract: Naturally occurring isoquinolones have gained considerable attention over the years for their bioactive properties. While the late-stage introduction of various functionalities at certain positions, namely, C-3, C-4, and C-8, has been widely documented, the straightforward introduction of challenging sp 3 carbon-linked acyclic aminoalkyl or aza- and oxacyclic appendages at C-6 and C-7 remains largely underexplored. Interest in 6-substituted azacyclic analogues has recently garnered atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 125 publications
0
8
0
Order By: Relevance
“…The construction of a related series by employing relevant cross-coupling protocols for 6-bromosubstituted analogs is a future goal. [18]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The construction of a related series by employing relevant cross-coupling protocols for 6-bromosubstituted analogs is a future goal. [18]…”
Section: Discussionmentioning
confidence: 99%
“…The ability to chemoselectively react with the isoquinolinone motif has led to a diverse array of compounds that exhibit biological activity [17] . For example, modification at the C‐6 position of isoquinolones with sp 3 hybridized moieties has enabled the creation of inhibitors of Rho kinase and compounds that display significant activity against KRAS G12C‐mutant cancer cells, previously described as “undruggable” targets [18] …”
Section: Introductionmentioning
confidence: 99%
“…The data underlying this study are available in the published article and its online Supporting Information. 35 Separate from those studies, Hegui Gong and co-workers have demonstrated pyridines are suitable monodentate ligands for nickel. 58,59 Coordination sphere modification via starting material-, intermediate-, or product-nickel chelation may inhibit productive catalysis (e.g., Figure 2; entries 1, 9, and 10).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…56 Despite all tested ligands successfully catalyzing the desired transformation, dtbbpy (4) was selected for further experimentation due to its generality across (hetero)aryl halide substrates (Figure 3a). 35,36,38,39 5-Fluoro-4-iodo pyridine and 5-fluoro-4-iodo-2-methylpyridine gave products 13 and 14 in 55% and 32% yield, respectively. 77 The yield for 14 was improved to 67% by inversing the stoichiometry of NHP ester (1 equiv) and 5-fluoro-4-iodo-2-methylpyridine (3 equiv).…”
Section: T H Imentioning
confidence: 99%
See 1 more Smart Citation